Gas molecular en la nebulosa anillo alrededor de WR 16 - Duronea, Nicolás Urbano (2009)
Using NANTEN 12CO (J=1→ 0) observations, the distribution of the molecular gas towards the multiple ring nebula sorrounding the star WR 16 has been analysed. Two striking features associated with the star and the nebula, respectively, were identified. One of them, the external one, is interstellar molecular gas which has been wind shaped in an early stage of the star. The internal feature is only noticed in a very small velocity range and has probably a stellar origin. Physical parameters have been calculated and kinematical models have been constructed in order to explain the physical link between these features and the nebula.